The role of the cryosphere for runoff in a highly glacierised alpine catchment, an approach with a coupled model and in situ data - Astrid Lambrecht; Christoph Mayer (Journal of Glaciology)
Runoff from heavily glacierised catchments, its seasonality and the contribution from different storage units are highly relevant for assessing the seasonal and long-term water supply and flood prediction. Modelling studies on runoff from such basins often use simulated meteorological input (e.g. downscaling products) based on remote observations. We investigate the contribution of snow, firn and ice to runoff in the Vernagtferner basin (Ötztal Alps) from 2020 to 2022, using a physical modelling chain driven by a local observation network. We use the SNOWPACK model to simulate snow/ice development at observation sites and the Alpine3D model to calculate accumulation and melt at the catchment scale. Basin discharge is estimated using a gridded version of the HBV-ETH model. This approach largely reproduces observed glacier mass balances, while modelled and measured basin discharge are in good agreement. Snowmelt dominates discharge in the early melt season, while ice melt becomes increasingly important during summer. This is in strong contrast to the near-equilibrium mass balances in the 1980s, when ice melt played a minor role for annual discharge. The strong reduction of the accumulation area leads to a fundamental change from a snowmelt regime to an ice melt regime, which is especially pronounced in 2022.